Natal habitat and sex-specific survival rates result in a male-biased adult sex ratio. (22nd February 2019) - Loonstra, A H Jelle; Verhoeven, Mo A; Senner, Nathan R; Hooijmeijer, Jos C E W; Piersma, Theunis; Kentie, Rosemarie
Abstract: The adult sex ratio (ASR) is a crucial component of the ecological and evolutionary forces shaping the dynamics of a population. Although in many declining populations ASRs have been reported to be skewed, empirical studies exploring the demographic factors shaping ASRs are still rare. In this study of the socially monogamous and sexually dimorphic Black-tailed Godwit ( Limosa limosa limosa ), we aim to evaluate the sex ratio of chicks at hatch and the subsequent sex-specific survival differences occurring over 3 subsequent life stages. We found that, at hatch, the sex ratio did not deviate from parity. However, the survival of pre-fledged females was 15–30% lower than that of males and the sex bias in survival was higher in low-quality habitat. Additionally, survival of adult females was almost 5% lower than that of adult males. Because survival rates of males and females did not differ during other life-history stages, the ASR in the population was biased toward males. Because females are larger than males, food limitations during development or sex-specific differences in the duration of development may explain the lower survival of female chicks. Differences among adults are less obvious and suggest previously unknown sex-related selection pressures. Irrespective of the underlying causes, by reducing the available number of females in this socially monogamous species, a male-biased ASR is likely to contribute to the ongoing decline of the Dutch godwit population. Abstract : Skewed adult sex ratios (ASRs) may affect population dynamics and sexual selection. We report a male-biased ASR in Black-tailed Godwits that results from male-biased survival during the pre-fledging period and adulthood. The relative difference in sex-specific survival during pre-fledging was higher in low-quality habitats. Our study demonstrates how both habitat-dependent and independent demographic processes acting at different life-history stages can influence the number of males and females available to reproduce in a population.